Influence of individual proton pump inhibitors on clinical outcomes in patients receiving clopidogrel following percutaneous coronary intervention. Issue 52 (30th December 2021) - Lee, Dongyoung; Kim, Je Sang; Kim, Beom Jin; Shin, Seung Yong; Kim, Dong Bin; Ahn, Hyung Sik
Abstract: Background: Data are conflicting on whether proton pump inhibitors (PPIs) diminish the efficacy of clopidogrel. We investigated individual PPIs and adverse cardiovascular events in postpercutaneous coronary intervention (PCI) patients on dual antiplatelet therapy with clopidogrel. Methods: We searched Ovid-MEDLINE, EMBASE, and Cochrane from inception to March 2020 to identify studies that evaluated the efficacy and safety of clopidogrel added PPIs versus clopidogrel only in post-PCI patient. We extracted data from 28 studies for major adverse cardiovascular endpoints (MACE), myocardial infarction (MI), cardiovascular death, and gastrointestinal bleeding. Risk ratios (RR) and hazard ratios (HR) were pooled separately. Results: Data were extracted on 131, 412 patients from the 28 studies included. Concomitant use of PPI with clopidogrel was associated with increased risk of MACE (RR 1.30; 95% confidence interval [CI] 1.15–1.48; P  < .001) and MI (RR 1.43; 95% CI 1.25–1.64; P  < .001). Random-effects meta-analyses with individual PPIs demonstrated an increased risk of MACE in those taking pantoprazole (RR 1.31; 95% CI 1.07–1.61, P  = .01) or lansoprazole (RR 1.35; 95% CI 1.19–1.54, P  < .0001) compared with patients not on PPIs. Likewise, in adjusted analyses, the pooled HR of adjusted events for MACEs showed that the increased risk of MACEs was similar for 4 classes of PPIs but not for rabeprazole (HR: 1.32; 95% CI 0.69–2.53, P  = .40). Conclusion: The post-PCI patients on dual antiplatelet therapy with clopidogrel in the PPI group were associated with higher risk of MACE and MI. Although the results for rabeprazole were not robust, it was the only PPI that did not yield a significantly increased risk of MACE. Abstract : Supplemental Digital Content is available in the text